Calcium gluconate as cross-linker improves survival and shelf life of encapsulated and dried Metarhizium brunneum and Saccharomyces cerevisiae for the application as biological control agents. (2nd January 2017) - Humbert, Pascal; Przyklenk, Michael; Vemmer, Marina; Patel, Anant V.
Abstract: Calcium chloride (CC) is the most common cross-linker for the encapsulation of biocontrol microorganisms in alginate beads. The aim of this study was to evaluate if calcium gluconate (CG) can replace CC as cross-linker and at the same time improve viability after drying and rehydration, hygroscopic properties, shelf life and nutrient supply. Hence, the biocontrol fungi Metarhizium brunneum and Saccharomyces cerevisiae were encapsulated in Ca-alginate beads supplemented with starch. Beads were dried and maximum survival was found in beads cross-linked with CG. Beads prepared with CG showed lower hygroscopic properties, but a higher shelf life for encapsulated fungi. Moreover, we demonstrated that gluconate has a nutritive effect on encapsulated fungi, leading to increased mycelium growth of M. brunneum and to enhanced CO2 release from beads containing Saccharomyces cerevisiae . The application of CG as cross-linker will pave the way towards increasing drying survival and shelf life of various, especially drying-sensitive microbes.